2020
DOI: 10.1017/jns.2020.14
|View full text |Cite
|
Sign up to set email alerts
|

The role of oligosaccharides and polysaccharides of xylan and mannan in gut health of monogastric animals

Abstract: Apart from its role as a digestive and absorptive organ, the gastrointestinal (GI) tract is a vital immune organ that encompasses roughly 70 % of the total immune cells of the body. As such, the physical, chemical and nutrient composition of the diet influences overall GI function, effectively as an immune organ. With the improvement in feed technology, agro-industrial co-products that are high in fibre have been widely used as a feed ingredient in the diets of pigs and poultry. Arabinoxylan (AX) and mannan ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 77 publications
0
28
0
Order By: Relevance
“…In particular, butyrate presence increased significantly, which has been shown to have anti-inflammatory effects and inhibit pathogenic bacterial colonization in the intestine. Similarly, arabinoxylooligosaccharides promote bifidobacterial growth in the cecum of chickens and aids in maintaining gut health [ 107 ], which is beneficial during Salmonella Enteritidis challenge. Infected birds fed a diet supplemented with either 0.4% or 0.2% arabinoxylooligosaccharides from wheat bran show decreased Salmonella populations in the ceca and spleen [ 108 ].…”
Section: Effects Of Dietary Fiber On the Immune Systemmentioning
confidence: 99%
“…In particular, butyrate presence increased significantly, which has been shown to have anti-inflammatory effects and inhibit pathogenic bacterial colonization in the intestine. Similarly, arabinoxylooligosaccharides promote bifidobacterial growth in the cecum of chickens and aids in maintaining gut health [ 107 ], which is beneficial during Salmonella Enteritidis challenge. Infected birds fed a diet supplemented with either 0.4% or 0.2% arabinoxylooligosaccharides from wheat bran show decreased Salmonella populations in the ceca and spleen [ 108 ].…”
Section: Effects Of Dietary Fiber On the Immune Systemmentioning
confidence: 99%
“…Polysaccharides, as natural active polymers, are widely present in plants and microorganisms. In recent years, polysaccharides have attracted great attention in investigating alternative growth promoters in animals [ 17 ]. For instance, numerous studies observed that dietary medicinal plant-derived polysaccharides could enhance immune function [ 18 ], elevate antioxidant capacity [ 19 ], improve intestinal barrier function [ 20 , 21 , 22 ], thus promoting the growth performance of broilers.…”
Section: Introductionmentioning
confidence: 99%
“…The free sugar contents in MCM were mainly mannobiose sugars (10.3%) and others were glucose, mannose, fructose, sucrose and mannotriose. Among those sugars, mannobiose has been reported for their important role as an immune modulator (Patel & Goyal 2012; Tiwari et al 2020). For instance, mannobiose is able to activate innate immune response in chicken under in vivo and in vitro studies (Agunos et al 2007; Duarte et al 2014; Ibuki et al 2010; Ibuki et al 2011).…”
Section: Resultsmentioning
confidence: 99%